2013
DOI: 10.1113/expphysiol.2013.075200
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptor inhibition attenuates the decrease in cutaneous vascular conductance during whole‐body cooling from hyperthermia

Abstract: New Findings r What is the central question of this study?Adenosine has been implicated in mediating both vasoconstriction and vasodilatation in a variety of tissues throughout the body. No study has yet examined its influence in cutaneous vasoconstriction elicited by whole-body cooling from normothermia or from hyperthermia. r What is the main finding and its importance?Through the use of the non-selective adenosine receptor antagonist, theophylline, a role for adenosine in the control of the cutaneous circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 27 publications
3
17
1
Order By: Relevance
“…Consistent with these findings (Swift et al . ), our results show that the infusion of THEO attenuated the decrease in cutaneous blood flow during recovery from exercise‐induced hyperthermia when compared to a control site. In fact, our data show that adenosine receptor activation may be a major contributor to the postexercise suppression in cutaneous blood flow (Fig.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Consistent with these findings (Swift et al . ), our results show that the infusion of THEO attenuated the decrease in cutaneous blood flow during recovery from exercise‐induced hyperthermia when compared to a control site. In fact, our data show that adenosine receptor activation may be a major contributor to the postexercise suppression in cutaneous blood flow (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…In keeping with animal studies, however, adenosine receptors have also been shown to modulate CVC during whole‐body cooling (Swift et al . ). This was evidenced by an attenuated decrease in CVC when adenosine receptors were inhibited during a bout of whole‐body cooling that was performed immediately following a passive heat stress.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Wong ; Swift et al. ). Moreover, we detected a vasoconstrictor effect of adenosine receptors on baseline CVC under low heat stress (Fieger and Wong ; McGinn et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Swift et al. ). However, it is important to note that the level of influence of NOS, COX, and adenosine receptors to cutaneous blood flow and sweating can vary based on the type and level of heating (Kellogg et al.…”
Section: Introductionmentioning
confidence: 98%